2011
DOI: 10.1128/aem.01564-10
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Listeria monocytogenes Dose Responses in Relation to Subtypes Encoding a Full-Length or Truncated Internalin A

Abstract: Internalin A (InlA; encoded by inlA) facilitates the crossing of the intestinal barrier by Listeria monocytogenes. Mutations leading to a premature stop codon (PMSC) in inlA and thus attenuated mammalian virulence have been reported. We recently characterized 502 L. monocytogenes food isolates from a retail survey and 507 human clinical isolates from multiple U.S. states with respect to the presence/absence of inlA mutations. The objective of this study was to investigate the hypothesis that dose responses for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…It has been suggested that certain PMSC mutations accumulate at the population level, with notable differences between PMSCs occurring in North America and those in European countries (19,20,25). Interestingly, we observed isolates with a type 11 (aa 685) PMSC mutation, which to date has not been reported outside France (19)(20)(21)39). It is well established that frameshift and transition/transversion mutations in inlA can lead to PMSCs, resulting in a truncated or nonsecreted InlA.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…It has been suggested that certain PMSC mutations accumulate at the population level, with notable differences between PMSCs occurring in North America and those in European countries (19,20,25). Interestingly, we observed isolates with a type 11 (aa 685) PMSC mutation, which to date has not been reported outside France (19)(20)(21)39). It is well established that frameshift and transition/transversion mutations in inlA can lead to PMSCs, resulting in a truncated or nonsecreted InlA.…”
Section: Discussionmentioning
confidence: 57%
“…Overall, 35% of strains possessed mutations in inlA due to PMSCs, a rate which is lower than that reported for food chain isolates in the United States (45%) (20,39) but similar to levels reported in France (40). In addition to previously described inlA mutations, including types 1, 3, 4, and 11, we observed inlA genotypes with a consecutive 3-codon deletion in the amino acid positions 738 to 740, a phenomenon to date reported only in a single isolate from a meat facility in Portugal (41).…”
Section: Discussionmentioning
confidence: 59%
“…The A 6 allele was significantly (P Ͻ 0.0001) overrepresented among food isolates, which is consistent with our previous study (31); conversely, the A 7 allele was significantly (P ϭ 0.0015) underrepresented among these strains. Interestingly, a previous study also showed that the average L. monocytogenes dose per positive serving was 3 ϫ 10 6 CFU/ serving for DUP-1039C with the 5= inlA frameshift mutation (i.e., the A 6 allele), which was Ͼ1,000-fold higher than those for other subtypes, including ribotype DUP-1039C, expressing full-length InlA (2.0 ϫ 10 3 CFU/serving), and ribotype DUP-1042B, representing an epidemic clone (9.0 ϫ 10 2 CFU/serving) (21). This indicates that isolates with the A 6 allele are not only more frequent among RTE food isolates but also typically found at higher levels in RTE foods than other subtypes, including subtypes commonly implicated in sporadic and epidemic listeriosis.…”
Section: Resultsmentioning
confidence: 99%
“…The virulence factor internalin A (InlA; encoded by inlA) facilitates the crossing of the host intestinal barrier, which enables subsequent establishment of a systemic infection by L. monocytogenes (20). L. monocytogenes isolates carrying a PMSC in inlA produce a truncated form of InlA that is secreted rather than anchored to the bacterial cell wall; these strains have been shown to be virulence attenuated in a guinea pig model (17,(21)(22)(23). A number of studies specifically indicate that lineage II strains carry an inlA PMSC more frequently than lineage I strains (18,23,24).…”
mentioning
confidence: 99%
“…Specifically, exponential models based on L. monocytogenes concentrations found in samples from retail sources generated mean log 10 r values of Ϫ8.1 and Ϫ10.7 for (i) subtypes encoding a fulllength InlA and (ii) subtypes carrying a PMSC in inlA, respectively. Inclusion of an additional parameter to estimate the increase in L. monocytogenes concentration between that in retail source samples and that from consumption resulted in mean log 10 r values of Ϫ10.44 and Ϫ13.75 for subtypes encoding a full-length InlA and subtypes carrying a PMSC in inlA, respectively (4). Findings from the current study provide further quantitative evidence that L. monocytogenes subtypes vary in their ability to cause a systemic L. monocytogenes infection, which may be mechanistically attributed to a defined genetic marker (i.e., presence of a mutation leading to a PMSC in inlA).…”
Section: Resultsmentioning
confidence: 99%